2016
DOI: 10.24953/turkjped.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-esteem in adolescents with a psychiatric referral

Abstract: In the literature self-esteem is found to be lower in clinically referred adolescents compared to adolescents without any psychiatric disorder. The aim of this study is to examine self-esteem and associated socio-demographical and psychological factors in clinically referred adolescents in Turkey. Three hundred forty-nine adolescents aged between 12 and 18 years admitted to the Department of Child and Adolescent Psychiatry with a psychiatric complaint were enrolled. Rosenberg Self-Esteem Scale (RSES), Brief Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
(25 reference statements)
0
8
0
1
Order By: Relevance
“…Previous studies in different parts of the world showed that authoritative parents are more likely to encourage their children and engage in their school activities [46]. Parental involvement [8,16], parental acceptance and support [24,64,83], and having a good relationship with their children [37,70,72] are beneficial for their children's self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in different parts of the world showed that authoritative parents are more likely to encourage their children and engage in their school activities [46]. Parental involvement [8,16], parental acceptance and support [24,64,83], and having a good relationship with their children [37,70,72] are beneficial for their children's self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Good psychosocial health in adolescence includes having a positive sense of identity and self-worth [6]. In this regard, self-esteem is an important aspect of mental health and it is believed to be one of the predictive factors for the psychological well-being of adolescents in their unique period of identity development [7][8][9][10]. Self-esteem is the overall subjective appraisal of oneself, i.e., positive, negative and mixed thoughts or feelings about one's own self, and if one has more positive feelings or considers oneself as worthy, self-esteem will be higher [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with health (Jafflin et al, 2019), personal and professional burnout (Kupcewicz & Jóźwik, 2020), mental health (Curvis et al, 2018), academic performance and achievement (Christy & Mythili, 2020), and victimization and perpetration of bullying (Jankauskiene et al, 2008). A study found nonsuicidal self-injury and sense of identity assessment form scores in adolescents to be predictive of self-esteem (Akdemir et al, 2016). A meta-analysis of studies also indicates that self-esteem is negatively associated with aggression (Teng et al, 2015) and depression and anxiety (Orth & Robins, 2013;Sowislo & Orth, 2013).…”
Section: Self-esteemmentioning
confidence: 99%
“…Because BI has been associated with gender, age, BMI and support from peers or family [ 13 , 14 ], positive SE has been associated with higher education level and male gender [ 15 , 16 ], and reduced QoL has been associated with disease activity and phenotype [ 17 ], CD patients with and without APF were subjected to propensity score matching (PSM). Propensity scores were based on baseline variables, including age, gender, educational level, marital status, family income level, BMI level, disease classification and HBI index.…”
Section: Methodsmentioning
confidence: 99%